2023
DOI: 10.5027/andgeov50n1-3459
|View full text |Cite
|
Sign up to set email alerts
|

On the validity of the Macrochorobates scalabrinii Biozone (early Huayquerian Stage/Age, Late Miocene). Multi-proxy analysis of the enigmatic Arenas Blancas site (Buenos Aires Province, Argentina)

Abstract: Arenas Blancas is a poorly known fossiliferous site located in the lower reach of the Chasicó creek (Buenos Aires Province, Argentina), with great relevance from a biostratigraphic viewpoint. The Macrochorobates scalabrinii Biozone was defined in this site, proposed as the biostratigraphic basis of the early Huayquerian Stage/Age (Late Miocene); however, the geological context and faunal record of this site have never been studied in detail. In this work, we perform a multi-proxy analysis of the Arenas Blancas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The collection number and the exact locality where the specimen mentioned in Piñero et al (2021) was found are not provided; there is no basis for the correlation between the lithofacies association 3 of Zárate et al , (2007) and the Las Barrancas Member of Fidalgo et al , (1978, 1987) since the former study contradicts the lithostratigraphic schema of the latter. Finally, the provenance of other specimens of Chasichimys in the context of Zárate et al , (2007) schema was not discussed, and more recently, Tomassini et al (2023) stated that with a large sample of mammals with good stratigraphic provenance no faunisitic differences were found throughout the sequence of the Arroyo Chasicó Formation. Therefore, we consider it premature to accept as an observational fact the occurrence of superposed levels in the Arroyo Chasicó sequence containing Ch .…”
Section: Resultsmentioning
confidence: 99%
“…The collection number and the exact locality where the specimen mentioned in Piñero et al (2021) was found are not provided; there is no basis for the correlation between the lithofacies association 3 of Zárate et al , (2007) and the Las Barrancas Member of Fidalgo et al , (1978, 1987) since the former study contradicts the lithostratigraphic schema of the latter. Finally, the provenance of other specimens of Chasichimys in the context of Zárate et al , (2007) schema was not discussed, and more recently, Tomassini et al (2023) stated that with a large sample of mammals with good stratigraphic provenance no faunisitic differences were found throughout the sequence of the Arroyo Chasicó Formation. Therefore, we consider it premature to accept as an observational fact the occurrence of superposed levels in the Arroyo Chasicó sequence containing Ch .…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with Tomassini et al . (2023), who recently rejected the validity of this biozone based on taphonomical and taxonomical studies in the type locality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, taphonomic analyses have begun to be applied as a complementary tool to understand how osteoderms have been modified by taphonomic processes and, on this basis, to solve taxonomic issues involving Cenozoic representatives of this group. These studies have proposed that some taxa of glyptodonts (Urotherium antiquum, U. simplex, Paraglyptodon chapadmalensis, Trachycalyptus chapadmalensis, Lomaphorus chapalmalensis) were identified and characterized based on osteoderms affected by different processes (i.e., weathering, abrasion, soil corrosion) that modified the original ornamentation patterns and, therefore, resulted in taxonomic misidentifications (Zurita et al 2016(Zurita et al , 2017Barasoain et al 2022;Tomassini et al 2023).…”
Section: Introductionmentioning
confidence: 99%